The workshop-houses of the Colombier hill (Ardèche) - Nicolas Minvielle Larousse; Isabelle Commandré; Magali Fabre; Julien Flament; Bernard Gratuze; Guergana Guionova; Jérôme Ros; Olivier Thuaudet (Archéologie Médiévale)
The Colombier hill, located in the Chassezac valley (Ardèche, France), had been temporarily occupied during the High Middle Ages (11th and 12th centuries) in order to mine from a silver-lead vein. Adjoining the mining networks, a building was erected. After several years of excavation, a conclusion has been reached, characterizing the hill’s occupancy and establishing its functions. Building on an archaeological and morphological study, as well as the examination of the artefacts originating from the building (stone tools, slag, pottery, glass, fauna, natural resources, manufactured objects), it has been possible to identify it as a mining site, built in order to process the ore and assist the workers. It was seemingly composed of workshop-houses that were regularly inhabited by small mining companies.